2006
DOI: 10.1289/ehp.8549
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Onset of Spring and Elevated Atmospheric CO 2 on Ragweed ( Ambrosia artemisiifolia L.) Pollen Production

Abstract: Increasing atmospheric carbon dioxide is responsible for climate changes that are having widespread effects on biological systems. One of the clearest changes is earlier onset of spring and lengthening of the growing season. We designed the present study to examine the interactive effects of timing of dormancy release of seeds with low and high atmospheric CO2 on biomass, reproduction, and phenology in ragweed plants (Ambrosia artemisiifolia L.), which produce highly allergenic pollen. We released ragweed seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
158
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(167 citation statements)
references
References 31 publications
6
158
0
3
Order By: Relevance
“…This is because Ambrosia seeds require moist chilling (stratification) before they can germinate (Pickett and Baskin 1973;Willemsen 1975;Baskin 1977, 1980). Ambrosia plants that emerge earlier have been shown to grow larger, and Ambrosia pollen production is directly correlated with biomass (Rogers et al 2006;Fumanal et al 2007). In addition, lower temperatures in June may facilitate reproductive growth because, as seen with chrysanthemums (close relatives to both Ambrosia), exposure to high temperatures at the beginning of the short-day period results in a notable delay both in initiation and further (Cockshull and Kofranek 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This is because Ambrosia seeds require moist chilling (stratification) before they can germinate (Pickett and Baskin 1973;Willemsen 1975;Baskin 1977, 1980). Ambrosia plants that emerge earlier have been shown to grow larger, and Ambrosia pollen production is directly correlated with biomass (Rogers et al 2006;Fumanal et al 2007). In addition, lower temperatures in June may facilitate reproductive growth because, as seen with chrysanthemums (close relatives to both Ambrosia), exposure to high temperatures at the beginning of the short-day period results in a notable delay both in initiation and further (Cockshull and Kofranek 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its wellrecognized association with allergic disease, a number of studies have demonstrated a probable role between climate change (i.e., rising CO 2 and temperature), phenology, and pollen production of common ragweed (29)(30)(31). However, these links were established at the laboratory level (30) and as a function of urbanization (27).…”
Section: Discussionmentioning
confidence: 99%
“…Shifts in plant populations have already been documented as a result of climate change (Rogers et al, 2006;Root et al, 2003;Singer et al, 2005). For example, studies show that increasing concentrations of CO 2 enhance the production of Amb a 1 allergen and pollen from ragweed (Ambrosia artemisiifolia L.) (Rogers et al, 2006;Singer et al, 2005).…”
Section: Allergenicitymentioning
confidence: 99%
“…For example, studies show that increasing concentrations of CO 2 enhance the production of Amb a 1 allergen and pollen from ragweed (Ambrosia artemisiifolia L.) (Rogers et al, 2006;Singer et al, 2005). In addition, diesel exhaust, which contains numerous pollutants, including PM, NOx, VOCs, CO, and polycyclic aromatic hydrocarbons (PAHs), has been shown to enhance allergenicity and asthma symptoms in adults and children by acting synergistically with allergens (D' Amato et al, 2002;Diaz-Sanchez et al, 2003;Janssen et al, 2003).…”
Section: Allergenicitymentioning
confidence: 99%